2012
DOI: 10.3928/19404921-20120906-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Two Protocols for Treating Nursing Home Residents with Advanced Dementia

Abstract: The Serial Trial Intervention (STI) is a decision support tool to address the problem of under assessment and treatment of pain and other unmet needs of people with dementia. This study compared the effectiveness of the 5-step and 9-step versions of the STI using a two-group repeated measures quasi-experimental design with randomization of 12 matched nursing homes. The sample consisted of 125 residents with moderate to severe dementia. Both the 5 and 9-step STIs significantly decreased discomfort and agitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Examples of agitated behaviors included restlessness, pacing, repetitive questioning, and hitting. Measures of agitation using these procedures have been responsive to change in previous intervention studies (Kovach et al, 2006;Kovach et al, 2012). Aff ect.…”
Section: Measurementmentioning
confidence: 93%
“…Examples of agitated behaviors included restlessness, pacing, repetitive questioning, and hitting. Measures of agitation using these procedures have been responsive to change in previous intervention studies (Kovach et al, 2006;Kovach et al, 2012). Aff ect.…”
Section: Measurementmentioning
confidence: 93%
“…Oxytocin release from the paraventricular nucleus in response to such sensory stimulation is a mechanism that has linked self-soothing behaviors to positive eff ects (Uvnäs-Moberg, Handlin, & Petersson, 2015). Exiting behavior by individuals with dementia is oft en an attempt to escape pain or relieve discomfort from a full bladder (Kovach et al, 2012). Th e view that individuals with dementia who resist being moved have problematic psychological behavior has been replaced by the view that resistance to movement is actually an adaptive response to being undertreated for musculoskeletal pain that worsens with movement (Kovach et al, 2012).…”
Section: Self-management Behavior and Cognitive Impairmentmentioning
confidence: 99%
“…Exiting behavior by individuals with dementia is oft en an attempt to escape pain or relieve discomfort from a full bladder (Kovach et al, 2012). Th e view that individuals with dementia who resist being moved have problematic psychological behavior has been replaced by the view that resistance to movement is actually an adaptive response to being undertreated for musculoskeletal pain that worsens with movement (Kovach et al, 2012). A pilot study of a mindfulness intervention, also reported in this issue of RGN, provides evidence that emotion regulation through mindfulness activities may positively aff ect short-term mood and behavior of those with CI (Kovach, Evans, Sattell, Rosenau, & Gopalakrishnan, 2018).…”
Section: Self-management Behavior and Cognitive Impairmentmentioning
confidence: 99%
“…The estimates of treatment effect used in this study are based on data from a parent study that compared the effects of two versions of a nursing assessment and treatment protocol (5-step and 9-step Serial Trial Intervention) on stress, pain, and agitation among NH residents with advanced dementia (Kovach et al, 2012). …”
Section: Background To Study Of People With Advanced Dementiamentioning
confidence: 99%
“…However, it was also found that thoughtful follow through was often lacking as evidenced by failure to get effective treatments scheduled for regular use and failure to add adjunctive and preventive therapies to the therapeutic regimen (Kovach, Cashin, et al, 2006). The 9-step version attempted to address these deficits by adding steps that directed nurses to provide more long-term and more comprehensive treatments and to perform more thorough evaluations (Kovach et al, 2012). …”
Section: Background To Study Of People With Advanced Dementiamentioning
confidence: 99%